2014
DOI: 10.1155/2014/980547
|View full text |Cite
|
Sign up to set email alerts
|

HO-1 Upregulation Attenuates Adipocyte Dysfunction, Obesity, and Isoprostane Levels in Mice Fed High Fructose Diets

Abstract: Background. Fructose metabolism is an unregulated metabolic pathway and excessive fructose consumption is known to activate ROS. HO-1 is a potent antioxidant gene that plays a key role in decreasing ROS and isoprostanes. We examined whether the fructose-mediated increase in adipocyte dysfunction involves an increase in isoprostanes and that pharmacological induction of HO-1 would decrease both isoprostane levels and adipogenesis. Methods and Results. We examined the effect of fructose, on adipogenesis in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 59 publications
5
38
2
Order By: Relevance
“…Treatment with SnMP tended to increase the levels of HO-1 mRNA and protein under all conditions, reaching significance for HO-1 in control and hemin treated cells (Fig 3.5b & c). This effect is consistent with other reports [214,243] and demonstrates the efficacy of the SnMP treatment. Similar results were observed for NQO1 and GCLM (Fig 3.5d & e).…”
Section: Co-treatment With a Ho-1 Inhibitor (Snmp) Does Not Prevent Tsupporting
confidence: 93%
See 2 more Smart Citations
“…Treatment with SnMP tended to increase the levels of HO-1 mRNA and protein under all conditions, reaching significance for HO-1 in control and hemin treated cells (Fig 3.5b & c). This effect is consistent with other reports [214,243] and demonstrates the efficacy of the SnMP treatment. Similar results were observed for NQO1 and GCLM (Fig 3.5d & e).…”
Section: Co-treatment With a Ho-1 Inhibitor (Snmp) Does Not Prevent Tsupporting
confidence: 93%
“…HO-1 induction remodels adipocytes, resulting in hyperplasia instead of hypertrophy. These adipocytes increase the production of AMPK, PPARγ, and adiponectin, at the same time decreasing the production of inflammatory markers and cytokines [209,210,215,243].…”
Section: Ho-1 and Adipocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…During hypoxia mediated oxidative stress, cellular heme is released and contributes to the growing "free heme pool. " Free heme is a potent pro-oxidant and increases ROS levels [48]. Elevated levels of heme are toxic and catalyze oxidative damage to cells, tissues, and organs.…”
Section: Gpdh (Mu/mg Protein)mentioning
confidence: 99%
“…Hence the role of HO-1 is vital which acts as the crucial enzyme catalyzing the heme degradation. Khitan and his colleagues [48] stated that the protective effect of HO-1 is ascribed to its role in decreasing the cellular heme content as they are highly toxic and leading to the generation of ROS and RNS. Similarly, in the present study increased HO-1 expression was observed in test adipocytes suggesting that HNE acts as a potent inducer of HO-1 to provide cytoprotective function which was similar to the study reported by Iles and his colleagues [49].…”
Section: Gpdh (Mu/mg Protein)mentioning
confidence: 99%